КОМИЛ ИНСОН ҒОЯСИ ЭТНОПЕДАГОГИКАНИНГ АСОСИЙ МАСАЛАЛАРИ СИФАТИДА - Алламбергенов, Е.К. (SCIENCE and SOCIETY, 2022)
The article provides a comprehensive scientific and theoretical analysis of the period of creation of the Karakalpak folk epic "Shahriyor". It is also given the educational perspectives, and on the basis of these concepts it is concluded that the epic is one of the invaluable pedagogical heritage of the early Renaissance.